The role of nystagmus in silicone oil emulsification after pars plana vitrectomy and silicone oil injection for complex retinal detachment - Yilmaz, T.; Guler, M. (Sage Publications Ltd, 2008)
PURPOSE. The purpose of this study was to determine whether nystagmus has a role in silicone oil emulsification after pars plana vitrectomy and silicone oil injection for complex retinal detachment. METHODS. A retrospective review was conducted of the clinical and operative records of eight eyes with nystagmus that underwent pars plana vitrectomy and silicone oil injection for repair of retinal detachment associated with proliferative vitreoretinopathy. Three male (37.5%) and 5 female (62.5%) patients were included in this study. The mean age was 36.4 years (range, 19 to 54 years) and the mean follow-up time was 18.3 months (range, 5 to 49 months). RESULTS. Three eyes underwent combined lensectomy and vitrectomy. During the initial postoperative period, retinal attachment was obtained in 6 (75%) patients. Two of eight eyes required further surgery. Silicone oil emulsification occurred in all eyes to different degrees in the 1- to 3-month postoperative period. No inverse hypopyon was observed in any of patients. Three of eight eyes developed open angle glaucoma due to silicone oil emulsification before the silicone oil removal. In these patients, intraocular pressure was controlled successfully by medical therapy. Silicone oil removal was performed before the planned time because of early emulsification. After the removal of silicone oil, two of three eyes had established open angle glaucoma and medical therapy was maintained. After the removal of silicone oil, recurrent retinal detachment developed in two eyes and one of them developed phthisis bulbi. CONCLUSIONS. Silicone oil emulsification may develop earlier than expected in patients with nystagmus who underwent pars plana vitrectomy combined with silicone oil injection.
Keywords: emulsification; nystagmus; silicone oil